Reconnecting the Elwha River: Spatial Patterns of Fish Response to Dam Removal - Duda, Jeffrey J.; Torgersen, Christian E.; Brenkman, Samuel J.; Peters, Roger J.; Sutton, Kathryn T.; Connor, Heidi A.; Kennedy, Phil; Corbett, Stephen C.; Welty, Ethan Z.; Geffre, Anna; Geffre, Josh; Crain, Patrick; et al. (Frontiers in Ecology and Evolution, 2021)
The removal of two large dams on the Elwha River was completed in 2014 with a goal of restoring anadromous salmonid populations. Using observations from ongoing field studies, we compiled a timeline of migratory fish passage upstream of each dam. We also used spatially continuous snorkel surveys in consecutive years before (2007, 2008) and after (2018, 2019) dam removal during summer base flow to assess changes in fish distribution and density over 65 km of the mainstem Elwha river.. Before dam removal, anadromous fishes were limited to the 7.9 km section of river downstream of Elwha Dam, potamodromous species could not migrate throughout the river system, and resident trout were the most abundant species. After dam removal, there was rapid passage into areas upstream of Elwha Dam, with 8 anadromous species (Chinook, Coho, Sockeye, Pink, Chum, Winter Steelhead, Summer Steelhead, Pacific Lamprey, and Bull Trout) observed within 2.5 years. All of these runs except Chum Salmon were also observed in upper Elwha upstream of Glines Canyon Dam within 5 years. The spatial extent of fish passage by adult Chinook Salmon and Summer Steelhead increased by 50 km and 60 km, respectively, after dam removal. Adult Chinook Salmon densities in some previously inaccessible reaches in the middle section of the river exceeded the highest densities observed in the lower section of the river prior to dam removal. The large number (> 100) of adult Summer Steelhead in the upper river after dam removal was notable because it was among the rarest anadromous species in the Elwha River prior to dam removal. The spatial extent of trout and Bull Trout remained unchanged after dam removal, but their total abundance increased and their highest densities shifted from the lower 25 km of the river to the upper 40 km. Our results show that reconnecting the Elwha River through dam removal provided fish access to portions of the watershed that had been blocked for nearly a century.